IDENTIFIKASI TELUR SOIL TRANSMITTED HELMINT (STH) PADA TANAH PERSAWAHAN DI DESA SUKODONO MENGGUNAKAN METODE NATIF - Elsa Mega Suryani; Yuli Novianti Sunarko; Muhammad Sungging Pradana; Setyo Dwi Santoso; Nadiah Al Batati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2023)
Soil is a mineral material that has several unconsolidated forms which are located on the surface of the earth and have undergone several treatments. Soil-Transmitted Helminth (STH) is an intestinal nematode that in its life cycle requires a soil medium for the infective form to mature. worms are moist soil, shady, and protected from sunlight. This study aims to determine whether there is contamination of